Comparison of waste anesthetic gases in operating rooms with or without an scavenging system in a Brazilian University Hospital - Braz,Leandro Gobbo (2017)
Abstract Background and objectives Occupational exposure to waste anesthetic gases in operating room without active scavenging system has been associated with adverse health effects. Thus, this study aimed to compare the trace concentrations of the inhalational anesthetics isoflurane and sevoflurane in operating room with and without central scavenging system. Method Waste concentrations of isoflurane and sevoflurane were measured by infrared analyzer at different locations (near the respiratory area of the assistant nurse and anesthesiologist and near the anesthesia station) and at two times (30 and 120 min after the start of surgery) in both operating room types. Results All isoflurane and sevoflurane concentrations in unscavenged operating room were higher than the US recommended limit (2 parts per million), regardless of the location and time evaluated. In scavenged operating room, the average concentrations of isoflurane were within the limit of exposure, except for the measurements near the anesthesia station, regardless of the measurement times. For sevoflurane, concentrations exceeded the limit value at all measurement locations and at both times. Conclusions The exposure to both anesthetics exceeded the international limit in unscavenged operating room. In scavenged operating room, the concentrations of sevoflurane, and to a lesser extent those of isoflurane, exceeded the recommended limit value. Thus, the operating room scavenging system analyzed in the present study decreased the anesthetic concentrations, although not to the internationally recommended values.